SPIRITUAL HARMONIOUS GENERATION – THE FOUNDATION OF THE DEVELOPMENT OF THE FUTURE - Tashmetov Tuxtasin Xudаyberganovich (Journals Park Publishing, 2022)
It is necessary to unite the people towards the great future and glorious goals, to bring up a high-quality, harmonious generation, to educate them as mature people in every possible way, and to become one of the urgent tasks now. Only then will we achieve in perspective the upbringing of a spiritually harmonious person, a healthy generation. One of the priorities of our society is to educate a harmonious generation. After all, only spiritually competent people can create a great future.
Keywords: Society, harmonious, perfect person, upbringing